2018
DOI: 10.1002/jcp.26586
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatocellular carcinoma: Protection by melatonin

Abstract: Despite great scientific breakthroughs toward understanding the identity of human hepatocellular carcinoma (HCC) mechanistically, there are still no clinically efficient therapeutic methods for this cancer. Melatonin (N-acetyl-5-methoxytryptamine) is a multi-tasking hormone that has long been known for its anti-cancer activity against various human cancers including HCC, which is a focus of this review. PubMed database was searched for relevant articles with the keywords: hepatocellular carcinoma (HCC), melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 157 publications
(486 reference statements)
1
86
1
Order By: Relevance
“…Hepatocellular carcinoma (HCC) is a primary malignancy of the liver, and occurs predominantly in patients with underlying chronic liver disease and cirrhosis . HCC is now the third leading cause of cancer deaths worldwide due to its frequent metastasis and easy relapsing postoperatively . Exosomes can transfer oncogenic miRNAs, including miR‐122 and miR‐32‐5p, to sensitive HCC cells, thereby inducing resistance to chemotherapy.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC) is a primary malignancy of the liver, and occurs predominantly in patients with underlying chronic liver disease and cirrhosis . HCC is now the third leading cause of cancer deaths worldwide due to its frequent metastasis and easy relapsing postoperatively . Exosomes can transfer oncogenic miRNAs, including miR‐122 and miR‐32‐5p, to sensitive HCC cells, thereby inducing resistance to chemotherapy.…”
Section: Chemotherapymentioning
confidence: 99%
“…39 HCC is now the third leading cause of cancer deaths worldwide due to its frequent metastasis and easy relapsing postoperatively. 40 reported that lnc-ROR, a stress-responsive lncRNA, was selectively enriched by transforming growth factor beta in exosomes of HCC cells, and also regulated resistance to chemotherapy. 43 They also identified that exosomal lnc-VLDLR was significantly upregulated in HCC cells, and that it increased the expression level of ABCG2 (ATP-binding cassette, sub-family G member 2) to promote chemoresistance.…”
Section: Hepatocellular Cancermentioning
confidence: 99%
“…N‐acetyl‐5‐methoxytryptamine, melatonin (MT) for short, is initially considered as a pineal hormone in maintaining day‐light rhythm . Recently, gastrointestinal tract has also been shown to secrete melatonin during night and daytime . However, intense investigations have gradually overthrew traditional standpoints and recognized melatonin as a broad‐spectrum regulatory molecule in multiple physiological activities, including improvements of reproduction, remissions of intestinal dysbacteriosis, anti‐inflammation, and anti‐cancer efforts .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, melatonin has also been confirmed to protect liver during metabolic syndrome through various defined mechanisms . Melatonin triggers ER‐ and autophagy‐induced apoptosis in liver cancer, while it inhibits hepatocellular carcinoma proliferation and invasiveness via various transcription factors and signaling pathways . Notably, melatonin controls tumor‐generated exosomes to ameliorate the immune suppression of cancer cells, indicating that melatonin is able to regulate physiological state of hepatocytes via extrinsic pathways, particularly through exosomal modification .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation